2016
DOI: 10.1097/opx.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Refractive Errors in the INK Area, Durban, South Africa

Abstract: Approximately 57.3% of the population 35 years and older in the INK area of Durban were affected by refractive errors, with myopia, hyperopia, and astigmatism being significantly associated with sex. This study suggests that there is a need for interventions to alleviate refractive error in the INK area as well as in other communities affected by the lack of access to affordable services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…This is unlike the present study where the prevalence of hypermetropia was higher than the prevalence of myopia. Similar findings were reported from South Africa where it was observed that the prevalence of myopia was higher in males while prevalence of hypermetropia was higher in females [11]. In the present survey, the ratio of women to men among those examined is 1.43:1 and this could be responsible for the higher prevalence of hypermetropia.…”
Section: Spectacle Coveragesupporting
confidence: 90%
“…This is unlike the present study where the prevalence of hypermetropia was higher than the prevalence of myopia. Similar findings were reported from South Africa where it was observed that the prevalence of myopia was higher in males while prevalence of hypermetropia was higher in females [11]. In the present survey, the ratio of women to men among those examined is 1.43:1 and this could be responsible for the higher prevalence of hypermetropia.…”
Section: Spectacle Coveragesupporting
confidence: 90%
“…Astigmatism was common among clinic participants, with 18% of all participants having astigmatism of -1.50 D or worse (Table 7.). The prevalence by age group agrees with previously reported data 16,17,28,30 and overall prevalence is similar to that reported by Gomez-Salazar et al 16 in Baja California. This may be compared to a prevalence of astigmatism of 23% in all those aged 20-39 in the US and 20% of Mexican Americans in the same age group.…”
Section: Astigmatismsupporting
confidence: 91%
“…This is agreement with the prevalence of hyperopia in this age group in the Gomez-Salazar et al 16 study. In keeping with the hyperopic shift known to occur in older people, [28][29][30] hyperopia increased to 34% in participants over 40, a similar prevalence to that reported in Mexican patients by Gomez-Salazar et al 16 Prevalence of hyperopia in people over 40 has been reported to be 25% in population based studies in the US and Europe. 13,19…”
Section: Prevalence Of Hyperopiasupporting
confidence: 80%
“…In Nigeria, the prevalence of myopia and HM was 16.1% and 2.1%, respectively, among 13,599 adults aged over 40 years as per the Nigeria National Blindness and Visual Impairment Study [87]. In South Africa, the prevalence of myopia was 11.4% in 1939 adults aged over 35 years [88]. In the same vein, the prevalence of myopia was relatively low 14.4% among adults aged 35-55 years in MIROR Study in Colombia [89].…”
Section: Non-asian Countriesmentioning
confidence: 99%